2020
DOI: 10.3390/s20061604
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium (IV) Quantification in Technologically Relevant Media Using Potentiometric Sensor Array

Abstract: The quantification of plutonium in technological streams during spent nuclear fuel (SNF) reprocessing is an important practical task that has to be solved to ensure the safety of the process. Currently applied methods are tedious, time-consuming and can hardly be implemented in on-line mode. A fast and simple quantitative plutonium (IV) analysis using a potentiometric sensor array based on extracting agents is suggested in this study. The response of the set of specially designed PVC-plasticized membrane senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The sensors for the study were chosen among those previously developed for quantification of lanthanides and actinides in SNF process streams [5,6]. Table 1 shows the chemical structures of the employed ligands.…”
Section: Potentiometric Sensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sensors for the study were chosen among those previously developed for quantification of lanthanides and actinides in SNF process streams [5,6]. Table 1 shows the chemical structures of the employed ligands.…”
Section: Potentiometric Sensorsmentioning
confidence: 99%
“…Recently, a new application of multisensor systems was proposed related to a very challenging task of actinides and lanthanides quantification in technological solutions of spent nuclear fuel (SNF) reprocessing [5][6][7]. The analytical chemistry of such media is not trivial at all due to the following reasons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…48,49 Several studies were further devoted to modification of electrode surfaces for U analysis as an alternate choice but its preparation involves a complex procedure and is expensive, tedious, and time-consuming, which restricts its application in routine sample analysis. 50,51 Few studies 52−54 have reported the DESs as designer solvents for green analytical chemistry since these solvents are like liquid crystals in which the analyte molecules are fixed in the crystal. Hence, detection enhancement is possible through a phenomenon similar to the micellar-enhanced spectrometry detection generated by surfactants.…”
Section: ■ Introductionmentioning
confidence: 99%